Public policy of the Household Targeting System in the local registration units in the Junín region – Peru (Gestionar: revista de empresa y gobierno, 2022)
The Peruvian State implements social policies, which contribute to improving the quality of life of the population in a situation of vulnerability, through social programs, the beneficiaries are identified by the Home Targeting System (SISFOH), the objective of the investigation consists in explaining the relationship of the public policy (SISFOH) implemented in the Local Registration Units (ULE) of the Junín - Peru region. Method, the research was basic, descriptive level, non-experimental cross-sectional design and quantitative approach. 30 ULE managers in the Junín region were surveyed. Results: In the Junín region, 53% of those responsible for the ULE consider that the SISFOH policy is fully complied with, 42% of professionals who work in the ULE are university graduates between high school graduates and graduates, 44% of professionals mention that the trainings are suitable for the development of functions demanded by the ULE, 46% manifest the existence of overload of functions arguing the low budget that prevents the hiring of assistance personnel, 43% disagree with the amount assigned, which limits the development of functions of the ULE. Conclusion: at 95% statistical confidence, it is verified that there is a significant relationship between the SISFOH public policy implemented by the ULE of the Junín region, in the aspects of: human, budgetary and technological resources; municipal management; municipal authorities.
Keywords: public policy; targeting; households